STUDI KARAKTERISTIK DAN POTENSI BATU PURU SEBAGAI AGREGAT KASAR DALAM CAMPURAN BETON NORMAL - Irwan, Andesta Granitio (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2024)
Coarse aggregates in concrete play a crucial role in determining concrete quality. Limitations in the availability of coarse aggregate materials at a construction site often pose challenges in producing high-quality concrete. Utilizing local materials such as Batu Puru as coarse aggregates is seen as having good potential to replace the role of conventional Batu Granit in concrete mixes. This study identifies the characteristics and potential of Batu Puru in normal concrete mixes with compositions of 0%, 25%, 50%, and 100% compared to conventional coarse aggregates. Research findings indicate that Batu Puru contains 60% quartz and 40% magnetite mineral, resulting in its reddish color, with Batu Puru's strength being 8.7% lower than that of Batu Granit based on in-situ Schmidt Hammer tests. The high absorption and abrasion values of Batu Puru pose challenges in controlling concrete quality, affecting factors such as water-cement ratio and concrete curing time. The average compressive strength values of concrete samples are 17.93 MPa, 14.48 MPa, 16.33 MPa, and 16.56 MPa for compositions of 0%, 25%, 50%, and 100% respectively. These values meet the national standard compressive strength target of 14.53 MPa with a quality level of K-175. Concrete mix compositions closely resembling the control samples using Batu Granit as conventional coarse aggregates are achieved when using Batu Puru entirely as coarse aggregates, with a difference of approximately 7.64%.